2019
DOI: 10.1002/er.4387
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and optimization of Schizochytrium biodiesel production using Na+‐doped nanohydroxyapatite

Abstract: Summary The present work investigates the synthesis of a new and highly efficient sodium‐doped nanohydroxyapatite, as a heterogeneous catalyst for the production of fatty acid methyl esters from Schizochytrium algae oil. Sodium nitrate supported on nanohydroxyapatite catalyst was prepared using wet impregnation technique and calcinated at different temperatures. The synthesized nanocatalyst was characterized to determine the structural and morphological properties, using BET, XRD, TGA, FTIR, ICP, and TEM. Char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 46 publications
4
30
0
1
Order By: Relevance
“…It was observed that the CC variable obtained greater influence in the mass yield, under working conditions, followed by the castor oil:peanut oil ratio (OM), CC (linear) by AO (linear) and the alcohol:oil ratio (AO). Similar behavior was observed by Kolthaman and Varadappan when working with heterogeneous catalysis, via methyl methane from Schizochytrium algae oil using BBD, indicating significant influence of catalyst.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…It was observed that the CC variable obtained greater influence in the mass yield, under working conditions, followed by the castor oil:peanut oil ratio (OM), CC (linear) by AO (linear) and the alcohol:oil ratio (AO). Similar behavior was observed by Kolthaman and Varadappan when working with heterogeneous catalysis, via methyl methane from Schizochytrium algae oil using BBD, indicating significant influence of catalyst.…”
Section: Resultssupporting
confidence: 81%
“…It was observed that the CC variable obtained greater influence in the mass yield, under working conditions, followed by the castor oil:peanut oil ratio (OM), CC (linear) by AO (linear) and the alcohol:oil ratio (AO). Similar behavior was observed by Kolthaman and Varadappan 25 when working with heterogeneous catalysis, via methyl methane from Schizochytrium algae oil using BBD, indicating significant influence of catalyst. Karmakar et al 26 when working with basic catalysis via methylation in the biodiesel synthesis of castor beans, using Taguchi design observed that the factor that most influenced the synthesis was the alcohol:oil ratio, and the lowest influence was observed by the catalyst.…”
Section: Analysis Of Variancesupporting
confidence: 81%
See 1 more Smart Citation
“…The fossil fuels depletion and global pollution have led to a tremendous demand for renewable energy. Biodiesel, a biomass‐derived fuel, has been synthesized worldwide to replace petroleum because of its benefits, which include biodegradability, renewability, and low emissions of carbon monoxide, carbon dioxide, hydrocarbons, and particulate matter . Among biofuel sources, ethyl levulinate has received considerable attention because it can be blended with petrodiesel and can be used as an oxygenate additive to biodiesel .…”
Section: Introductionmentioning
confidence: 99%
“…Biodiesel, a biomass-derived fuel, has been synthesized worldwide to replace petroleum because of its benefits, which include biodegradability, renewability, and low emissions of carbon monoxide, carbon dioxide, hydrocarbons, and particulate matter. [1][2][3] Among biofuel sources, ethyl levulinate has received considerable attention because it can be blended with petrodiesel and can be used as an oxygenate additive to biodiesel. 4 In addition, ethyl levulinate is produced from levulinic acid, which is a chemical derived from lignocellulose biomass 5,6 and thus is a means of producing biofuel from renewable sources.…”
Section: Introductionmentioning
confidence: 99%